2023
DOI: 10.1101/2023.10.01.560400
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brassinosteroid recruits FERONIA to safeguard cell expansion in Arabidopsis

Ajeet Chaudhary,
Yu-Chun Hsiao,
Fang-Ling Jessica Yeh
et al.

Abstract: Plant cell expansion is driven by turgor pressure and regulated by hormones. How plant cells avoid cell wall rupture during hormone-induced cell expansion remains a mystery. Here we show that brassinosteroid (BR), while stimulating cell elongation, promotes the plasma membrane (PM) accumulation of the receptor kinase FERONIA (FER), which monitors cell wall damage and in turn attenuates BR-induced cell elongation to prevent cell rupture. The GSK3-like kinase BIN2 phosphorylates FER, resulting in reduced FER acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…In support of that notion, recent results in Arabidopsis identified posttranslational regulatory mechanisms affecting turgor-driven cell expansion ( Chaudhary et al., 2023 ). Specifically, the Arabidopsis receptor kinase FERONIA (FER) was implicated in regulating turgor-driven cell expansion in response to brassinosteroids, and FER is postranslationally regulated through phosphorylation by the BRASSINSTEROID-INSENSITIVE 2 kinase ( Chaudhary et al., 2023 ). However, we did find strong signatures of cell wall biosynthesis and modification-related genes associated with both vessel frequency and diameter ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In support of that notion, recent results in Arabidopsis identified posttranslational regulatory mechanisms affecting turgor-driven cell expansion ( Chaudhary et al., 2023 ). Specifically, the Arabidopsis receptor kinase FERONIA (FER) was implicated in regulating turgor-driven cell expansion in response to brassinosteroids, and FER is postranslationally regulated through phosphorylation by the BRASSINSTEROID-INSENSITIVE 2 kinase ( Chaudhary et al., 2023 ). However, we did find strong signatures of cell wall biosynthesis and modification-related genes associated with both vessel frequency and diameter ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 79%
“…enrichment of genes associated with turgor-related process at the level of GO analysis, which could reflect that this process is not globally regulated at the level of transcription. In support of that notion, recent results in Arabidopsis identified posttranslational regulatory mechanisms affecting turgor-driven cell expansion (Chaudhary et al, 2023). Specifically, the Arabidopsis receptor kinase FERONIA (FER) was implicated in regulating turgordriven cell expansion in response to brassinosteroids, and FER is postranslationally regulated through phosphorylation by the BRASSINSTEROID-INSENSITIVE 2 kinase (Chaudhary et al, 2023).…”
Section: Figurementioning
confidence: 95%
“…Whether RALF23 promotion of BRI1-BAK1 association and signaling is a consequence of RALF23-triggered changes in pectin or whether RALF23-triggered changes in pectin are partially mediated by BRI1 signaling remains to be clarified. Interestingly, a recent report showed that BR signaling modulates FER plasma membrane localization (Chaudhary et al 2023) indicating that RALF and BR signaling regulate each other providing a molecular circuit coordinating morphogenesis. In addition, more research is required to unravel whether RALF signaling also involves the previously identified BR-regulating wall monitoring cell-surface receptors RLP44 (Wolf et al 2014) and RFO1/WAKL22 (Huerta et al 2023), or whether they correspond to parallel signaling pathways converging towards BR signaling.…”
Section: Resultsmentioning
confidence: 99%